The relationships between aerobic fitness, power maintenance and oxygen consumption during intense intermittent exercise - Tomlin, DL; Wenger, HA (Journal of science and medicine in sport, 2002)
This study examined the relationships between VO 2max, power maintenance and oxygen consumption during intense intermittent work. Female recreational soccer players were assigned to either a low aerobic power group (LOW, n=6, mean (SD) VO 2max = 34.4 (2.4) mL·kg −1·min −1) or to a moderate aerobic power group (MOD, n=7, VO 2max = 47.6 (3.8) mL·kg −1·min −1). VO 2 was measured while subjects performed 10 6-s all-out sprints (30-s passive recovery) on a Monark cycle ergometer. LOW and MOD subjects generated similar peak 6-s power (p = .58) but MOD had a smaller decrement in power (% DO) over the 10 sprints (LOW vs MOD: 18.0 (7.6) vs 8.8 (3.7) % DO, p=.02). The MOD group also consumed significantly more oxygen than LOW in 9 of the 10 sprint-recovery cycles (p <.05). Significant relationships were seen between VO 2max and the aerobic response to the sprint-recovery series (r= .78, p=.002) as well as between VO 2max and % DO (r= −.65, p=.02), while a nonsignificant relationship was seen between the oxygen consumed during the sprint-recovery cycles and % DO (r= −.41, p=.16). Thus, VO 2max appears to be related to both an increased aerobic contribution to sprint-recovery bouts and the enhanced ability of the MOD group to resist fatigue during intense intermittent exercise.